The implementation of the Family Health Program (PSF) in the State of São Paulo (1995-2002) - Guedes, Jose da Silva; Santos, Rosa Maria Barros dos; Di Lorenzo, Rosicler A. Viegas (Saúde e Sociedade, 2011)
This article describes the development of Programa Saúde da Família (PSF - Family Health Program) in the State of São Paulo since its beginning until the year 2002. The background goes back to the mid 70s, when the Ministry of Health initiated a program to establish health care in distant undeveloped rural areas of the country. Other important antecedents were a similar program conducted by the government of the State of São Paulo in "Vale do Ribeira" from 1980 to 1987, and the National Program of Community Health Agents, carried out in the 1990s. The article also points out the influence of the São Paulo Metropolitan Region's Health Assistance Program conducted by the State Government and the engagement of activist social health organizations in the city of São Paulo. The description highlights the main characteristics of the PSF in the State of São Paulo and the team's composition in different periods of time. The Government of São Paulo used three different forms to support the development of the program: the first was technical advice and coordination, the second, technical and financial support to the municipalities, and the third was the partnership with non-profit health organizations to establish family health teams in the city of São Paulo. An evaluation of all the family health teams in the State of São Paulo, carried out in 2001, revealed great satisfaction of the assisted population and also examined different forms to engage or hire health professionals to work in family health teams. The development of the program is a consequence of the efforts to promote the qualification of the family health professionals, as well as the engagement of municipalities - especially those responsible for Public Health Administration, Universities and social health activism.